Activity of sotorasib against brain metastases from NSCLC harboring KRAS p.G12C mutation: a case report - Alessandro Inno; Fabiana Marchetti; Matteo Valerio; Niccolò Giaj Levra; Filippo Alongi; Giovanni Foti; Stefania Gori (AboutScience Srl, 2023)
In the CodeBreaK 100 phase 2 study, sotorasib was active for patients with metastatic non-small cell lung cancer (NSCLC) harboring Kirsten rat sarcoma viral oncogene homologue (KRAS) p.G12C mutation. However, patients with untreated and/or active brain metastases were excluded from the trial, and the activity of sotorasib in the setting of brain metastases should be further investigated. Here we report the case of a KRAS p.G12C mutant NSCLC patient with three brain metastases, of whom one was untreated and the other two had progressed after radiotherapy with symptoms requiring steroids, that responded to sotorasib. Our report suggests that sotorasib may be active against untreated or progressive brain metastases, supporting further evaluation of sotorasib in this setting.